Needs Analysis To Develop Heat Ict Based Teaching Material With Ethno-Pbl To Promote Students’ Critical And Creative Thinking Skills - Afifah, Afifah (Department of Physics Universitas Negeri Padang, 2025)
Critical and creative thinking skills are essential 21st-century competencies that students need to master. However, in reality, the mastery of these skills remains relatively low. This low level of skill is caused by the limited availability of teaching materials that are not yet integrated with Information and Communication Technology (ICT), ethnoscience, and the Problem-Based Learning (PBL) model. This study aims to analyze the needs for developing heat ICT-based teaching materials integrated with the ethno-PBL approach. The research method used is descriptive quantitative research. Data were collected through questionnaire instruments filled out by both the researcher and students. The results of the study revealed six key findings from the needs analysis: (1) the context of heat teaching materials scored 53.75; (2) the integration of ethnoscience into teaching materials scored 31.67; (3) the integration of the PBL model into teaching materials scored 48; (4) students' learning interest scored 57; (5) students' learning motivation scored 47; and (6) students' critical and creative thinking skills were still low, with scores of 39 and 36 respectively. The conclusion drawn from the needs analysis is that the development of heat ICT-based teaching materials integrated with the ethno-PBL approach is highly needed by senior high school students to support the enhancement of their critical and creative thinking skills.